Automatic Car Parking and Controlling System Using Programmable Logic Controller (PLC) - Ahamed, Nizam Uddin; Zulkifli, Md. Yusof; Al-Mamun, Md. Abdullah; Rahman, S. A. M. Matiur; Ahmed, Nasim; Hassnawi, L. A. (Research India Publications, 2015)
Well-organized vehicle parking can assist drivers gratifying by protecting car energy as well as time consuming. In this paper, the automation process of an automatic car parking system is designed using a fully functional ladder logic based LOGO!12/24 RC, which is a small programmable logic controller (PLC). Infrared sensor (IR) electronic sensors were installed at the entrance and departure gates to sense the car those are waiting for either entry or exit. After that it gives the input signals to PLC to count the number of vehicles entering and leaving the park respectively. The developed system automatically can monitor and restrict the vehicles inside the parking space. The number of cars available in the park will be the difference of the number of vehicles entering and the number of vehicles leaving. When a car approaches to the entry gate, PLC will decide whether any space is available or not. If no space is available, the PLC will then send signal to entry gate to keep the gate closed and turn on the indication “Car Park Full”. If there is space in the park, the entry gate will open to allow the car to enter the park. Similarly, at the time of exit, the PLC will send signal to the exit gate to open and allow the car to leave the park after paid the parking payment. All these activities make the car parking system completely automatic. The development of this system is cost effective and useful to make solutions to car parking space problems in city areas.